TROMBOSITOPENIA SEBAGAI PREDIKTOR KEMATIAN CEDERA KEPALA BERAT - , Tis'a Callosum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Severe traumatic brain injury is a primary cause of morbidity and mortality in the worldâs adult population. Several factors take parts in mortality in severe traumatic brain injury. One of them is thrombocytopenia. There is no such study about thrombocytopenia as a predictor of mortality in severe traumatic brain injury in Indonesia. This study aims at identifying thrombocytopenia as a predictor of mortality in severe traumatic brain injury. This study employs retrospective cohort method. Subjects of this study were collected from the medical records of inpatient care RSUP Sardjito from January 1st, 2011 to December 31st, 2012 using the method codes of S06.4, S06.5, S06.6, S06.7 and S06.8. Data was analyzed with Chi-square test, bivariate analysis, multivariate analysis, and logistic regression. Survival was analyzed by Kaplan Meier estimator. Eighty seven subjects satisfied the inclusion and exclusion criteria. Of that number, 43 had thrombocytopenia and 44 had normothrombocyte. Twenty six patients with thrombocytopenia died. In normothrombocyte group, 13 patients died. Thrombocytopenia is the statistically significant predictor of mortality in severe traumatic brain injury (p=0,004) in bivariate analysis, with RR 2.047 (95% CI 1.221- 3.43). Other statistically significant predictors of mortality in severe traumatic brain injury are Glasgow Coma Scale (GCS) score, hypertension, hypoalbumin, hyperglycemia, presence of subarachnoid hemorrhage (SAH) and intraventricular hemorrhage (IVH). Results of multivariate analysis suggest that thrombocytopenia is not an independent predictor of mortality in severe traumatic brain injury (p=0.119), with RR 2.582 (95% CI 0.783-8.512). Other statistically significant variables as the independent predictor of mortality in multivariate analysis in severe traumatic brain injury are GCS score, hypoalbumin and presence of SAH. It is concluded that thrombocytopenia is a non-independent predictor of mortality in severe traumatic brain injury. Key words : thrombocytopenia - severe traumatic brain injury - predictor - mortality